Bacterial reservoirs in cystic fibrosis. Issue 2 (February 1990) - Taylor, C J; McGaw, J; Howden, R; Duerden, B I; Baxter, P S
Abstract : To establish whether colonisation of the upper respiratory tract or bacterial contamination of inhaler devices or solutions predisposes to colonisation of the lower respiratory tract in patients with cystic fibrosis, bacterial isolates from groups of children who were positive (n = 13) or negative (n = 18) for Pseudomonas aeruginosa were studied. Cultures of swabs from inhaler devices, toothbrushes, and upper airways were compared with cough swabs or sputum cultures. No pathogens were obtained from inhaler equipment administering unit dose medications. Upper airway carriage of Staphylococcus aureus and Haemophilus influenzae was identified in both groups but correlated poorly with sputum isolates. P. aeruginosa was found only in the upper respiratory tract of children with established colonisation of the lower airways. No P aeruginosa isolates were obtained from the upper airways of the group with negative sputum, including one patient who became colonised by P aeruginosa during the study. Our results did not support the suggestion that colonisation of the upper respiratory tract by P aeruginosa predisposes to colonisation of the lower airways. Failure to isolate pathogenic organisms consistently from the upper airways in patients with positive sputum argues against a local epithelial factor predisposing to bacterial colonisation.